2021
DOI: 10.4314/ijbcs.v15i1.25
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and structure elucidation of anti-malarial principles from Terminalia mantaly H. Perrier stem bark

Abstract: Emergence of malaria parasite resistance to drugs has raised global public health concerns for a compelling need to develop improved malaria therapy. This study is a bio-guided isolation of triterpenoid antimalarial compounds from Terminalia mantaly. Methanol extract of the plant was subjected to column chromatography, and eluted with a ternary solvent system gradient-wise. Two compounds, 1 and 2, were isolated and characterised by spectroscopic data (IR, 1H and 13C NMR, COSY, HMQC, HMBC) and by comparison wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…This process is complicated to operate and requires costly chiral reagents and a longer reaction time with tedious workup (Nilesh, 2016). Thus, this study supports the synthesis of drugs as also reported in other studies (Bamba et al, 2021;Samuel and Adekunle, 2021;Kouamé et al, 2021;Chawe et al, 2021).…”
Section: Introductionsupporting
confidence: 92%
“…This process is complicated to operate and requires costly chiral reagents and a longer reaction time with tedious workup (Nilesh, 2016). Thus, this study supports the synthesis of drugs as also reported in other studies (Bamba et al, 2021;Samuel and Adekunle, 2021;Kouamé et al, 2021;Chawe et al, 2021).…”
Section: Introductionsupporting
confidence: 92%
“…Unfortunately, the precise mechanism of action is currently unexplained. The possible mechanism of triterpenoids as antimalarial action includes their impacts on mitochondrial membrane potential and the reduction of β-haematin synthesis [31][32][33]. Triterpenoid (betulinic acid) antimalarial activity is assumed to be related to its ability to engage the PfATP6 protein, which regulates calcium ion transportation and affects the host-parasite selectivity [34].…”
Section: Evaluation Of Inhibition Rate Percentage and Ic50mentioning
confidence: 99%